Resist to exist - PETRONE, ALESSANDRA (FrancoAngeli, 2024)
The book chronicles faithfully several months, from June to December 2004, during the Second Intifada, which the author spent in the Northern West Bank as a trainer for a group of Palestinian psychologists to help them cope with the trauma of war. The context is one where everyday life clashes/encounters with death, anger, and the pain of those who suffer violence and oppression daily, where these experiences and emotions coexist, paradoxically, with lightness and irony. The work describes interventions of Gestalt Psychotherapy and documents an anthropological field observation, participated and participant, more recently renewed in 2016, in the spirit of a concrete, attentive, and militant humanism. A first edition of the book was published in 2018. The significance of this reissue, in this particular historical moment, is twofold: on one hand, the book provides useful intervention tools to address traumatic situations, now unfortunately increasingly common on a global scale; on the other hand, following in the footsteps of Martin Buber and Hannah Arendt, it advocates for a resolution of this dramatic conflict based on dialogue rather than the use of weapons, on building bridges rather than walls.